2019
DOI: 10.3390/atmos10110639
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characterization of Brake-Wear Particles in a PM10 Dilution Tunnel

Abstract: A dilution tunnel was designed for the characterization of brake-wear particle emissions up to 10 µm on a brake dyno. The particulate matter emission levels from a single front brake were found to be 4.5 mg/km (1.5 mg/km being smaller than 2.5 µm) over a novel real-world brake cycle, for a commercial Economic Commission for Europe (ECE) pad. Particle Number (PN) emissions as defined in exhaust regulations were in the order of 1.5 to 6 × 10 9 particles per km per brake (#/km/brake). Concentration levels could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Several different approaches for sampling and measuring brake particle emissions have been proposed. These include studies at the brake component level on a pin-on-disc configuration [7,8], at the brake couple level on a brake dynamometer [9][10][11][12][13][14][15], and at full vehicle level both in the laboratory [16,17] and on-road [18,19]. Mathissen et al [17] summarised in detail the different setups applied for studying brake particle emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Several different approaches for sampling and measuring brake particle emissions have been proposed. These include studies at the brake component level on a pin-on-disc configuration [7,8], at the brake couple level on a brake dynamometer [9][10][11][12][13][14][15], and at full vehicle level both in the laboratory [16,17] and on-road [18,19]. Mathissen et al [17] summarised in detail the different setups applied for studying brake particle emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BWPs are a complicated mixture of metal and plastic. BWP emissions depend on the bulk friction material 23,26 , on the frequency and severity of braking 27 , speed, weight, condition and maintenance of the automobile 28 and the environmental conditions 23,29,30 .…”
mentioning
confidence: 99%
“…Similarly, the 3h-LACT yielded the same levels of PM 2.5 but distinctly higher PM 10 emissions, with the PM 10 /PM 2.5 ratio increasing from 3 to 3.6. Tests with other brake systems suggested that PM emission varies with the size of the brakes, with PM 2.5 over the last section of WLTP ranging between 1.5 mg/km and 4.1 mg/km, for two systems having an effective disc radius of 113 mm [32] and 144 mm [17], respectively. The PM 10 to PM 2.5 ratios for both brake systems (~2.7) were similar to what was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a reference, the inertial losses of 10 µm particles in a 90 • bend for the above duct sizes and flows would be 15% to 23% for 80 mm ducts and 8% to 11% for 175 mm ducts. In fact, a single 90 • bend is the major source of losses in the small tunnel [32], while the larger tunnel employed here incorporates two 90 • bends resulting eventually in similar losses. Overall, the effect of flow on particle losses is expected to be small at the conditions tested as confirmed by the gravimetric PM measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation